STUDY AND IDENTIFICATION OF WHEAT RESISTANCE MECHANISMS TO SALT STRESS IN THE BUKHARA REGION (Лучшие интеллектуальные исследования, 2025)
Abstract: the article presents data on the geographical location of the Bukhara region, the processes of wheat resistance to salt stress, and the survival of plants in the saline soils of the region.